Frequency of Rouviere's Sulcus and its Relation to the Dissection Time of Calot's Triangle - Faryal Sajid; Tariq Mukhtar Farani; Muhammad Waqas Ahmed Bhati; Mubashir Ahmad Toor; Fatima Farooq (Journal of the Dow University of Health Sciences)
Objective: To determine the frequency of Rouviere's Sulcus in patients undergoing laparoscopic cholecystectomy and assess its relationship with the dissection time of Calot's Triangle. Methods: A descriptive cross-sectional study was carried out at the Department of General Surgery, Combined Military Hospital, Quetta, Pakistan, from November 2024 to January 2025. All patients undergoing elective laparoscopic cholecystectomy for uncomplicated cholelithiasis were included using non-probability consecutive sampling. Intraoperative identification of Rouviere's Sulcus was performed and classified into open, closed, and slit types. The operative dissection time of Calot's Triangle was recorded from the insertion of the last port to clipping of the cystic duct and artery. Results: Among 52 patients, the median age was 34.5 (IQR 27-40) years. Rouviere's Sulcus was identified in 48 (92.3%) patients. Among visible Rouvière's Sulcus, the open type was most common 26 (54.2%), followed by closed 16 (33.3%) and slit types 6 (12.5%). Visibility was higher in patients ≤35 years 30 (100%) compared to >35 years 18 (81.8%). The median operative dissection time of Calot's Triangle was shorter in patients with visible Rouvière's Sulcus compared to those without 9.5 (8-13) vs. 14 (11-15) minutes. Conclusion: Rouviere's Sulcus was visible in the majority of elective laparoscopic cholecystectomy cases, with open type being most common. Its presence was related with reduced dissection time, underscoring its role as a critical anatomical landmark for safe cholecystectomy.